Efforts to Increase the Level of Service at Terminal 3 Domestic at Soekarno Hatta International Airport - Aziz Fahmi Harahap; Juliater Simarmata; Erman Noor (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The purpose of this study is (1) to determine and analyze the customer satisfaction index against the Level of Service; (2) to know and analyze the Level of Service factors considered important by the customer; (3) to identify and analyze the Level of Service gap between customer expectations and satisfaction; (4) to know and analyze the Level of Service factors that should be improved. The data collection method used a questionnaire with a sample of 201 respondents. The analysis method uses Gap Analysis, Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). Based on the results of CSI analysis, a value of 77.73 was obtained, the number was in the range of 60.01 – 80 which means satisfactory or good, while based on the results of the Importance Performance Analysis (IPA) analysis, 9 indicators were obtained which are still in quadrant one can be interpreted that these indicators have low reality and high expectations from Soekarno-Hatta International Airport terminal two.